The Internationalization of the firm : (a reader) - Buckley, Peter J., 1949-; Ghauri, Pervez N. (International Thomson Business Press, 1999)
The Internationalization of the Firm is a collection of seminal articles on international business with particular reference to the experience of large European and American multinationals in Europe, Japan and the developing countries.